Mosaic paternal uniparental isodisomy and an ABCC8 gene mutation in a patient with permanent neonatal diabetes and hemihypertrophy. - Shield, J; Flanagan, SE; Mackay, D; Harries, L; Proks, P; Girard, C; Ashcroft, F; Temple, I; Ellard, S (2008)
OBJECTIVE: Activating mutations in the KCNJ11 and ABCC8 genes encoding the Kir6.2 and SUR1 subunits of the pancreatic ATP-sensitive K(+) channel are the most common cause of permanent neonatal diabetes. In contrast to KCNJ11, where only dominant heterozygous mutations have been identified, recessively acting ABCC8 mutations have recently been found in some patients with neonatal diabetes. These genes are co-located on chromosome 11p15.1, centromeric to the imprinted Beckwith-Wiedemann syndrome (BWS) locus at 11p15.5. We investigated a male with hemihypertrophy, a condition classically associated with neonatal hyperinsulinemia and hypoglycemia, who developed neonatal diabetes at age 5 weeks. RESEARCH DESIGN AND METHODS: The KCNJ11 and ABCC8 genes and microsatellite markers on chromosome 11 were analyzed in DNA samples from the patient and his parents. RESULTS: A paternally inherited activating mutation (N72S) in the ABCC8 gene was identified in the proband. The mutation was present at 70% in the patient's leukocytes and 50% in buccal cells. Microsatellite analysis demonstrated mosaic segmental paternal uniparental isodisomy (UPD) of 11pter-11p14 in the proband that encompassed the ABCC8 gene and the BWS locus. CONCLUSIONS: We report a patient with neonatal diabetes, hemihypertrophy, and relatively high birth weight resulting from telomeric segmental paternal UPD of chromosome 11, which unmasks a recessively acting gain-of-function mutation in the ABCC8 gene and causes deregulation of imprinted genes at the BWS locus on 11p15.5.